Akses, Penggunaan Dan Faktor Penentu Pemanfaatan Teknologi Informasi Dan Komunikasi Pada Kawasan Pertanian Komersial Untuk Mendukung Ketahanan Pangan Di Perdesaan Yogyakarta - Subejo Subejo; Ratih Ineke Wati; Mesalia Kriska; Najmu Tsaqib Akhda; Ade Intan Kristian; Ani Dwi Wimatsari; Paksi Mei Penggalih (Universitas Gadjah Mada, 2018)
ABSTRACT Utilization of information and communication technologies (ICTs) had changed the diversity of agricultural extension and communication services which required alternatives for users of the services. Higher and better speed of information services was considerably recquired for supporting the sustainability of commercial farming business which in turn could facilitate the achievement of high status of food resilience. The goals of research were: (1). Describing access and function of ICTs for agricultural community, (2). Describing pattern on the usage of ICTs for supporting agricultural activities, (3). Analyzing the determinant factors on the usage of ICTs for supporting agricultural activities. The research method used in the study was analytical descriptive with survey research technique. The sites of study were commercial farming areas in Yogyakarta namely Patuk Gunungkidul, Turi Sleman, Sanden Bantul and Panjatan Kulon Progo. Sample were selected by using simple random sampling method. Data had been collected by using structured questionnaire, observation and indepth interview. While data analysis had been done by using descriptive statistic and multiple regression. Study results showed that (1). Ownership of ICTs media in all of research sites was considerably high including conventional media and new media which both had high capability providing information and entertaninment, but the function on education was still considerably limited, (2). Utilization of ICTs for supporting agricultural activities was: conventional media (television and radio) for providing information on technical production, policy and marketing, while new media (handphone and smartphone) for providing information on technical production, policy, marketing and financial aspect, (3). Determinant factors on ownership of ICTs were age and social status, and (4). Determinant factors on the usage of ICTs for supporting agricultural activities were age and sex of farmers.ABSTRAK Pemanfaatan Teknologi Informasi dan Komunikasi (TIK) menyebabkan adanya perubahan keragaman (diversifikasi) layanan penyuluhan dan komunikasi pertanian yang memberi alternatif lebih baik bagi para pengguna layanan. Kecepatan layanan informasi sangat diperlukan untuk mendukung keberlanjutan pertanian komersial sehingga pada gilirannya dapat berkontribusi pada pencapaian ketahanan pangan yang tinggi. Tujuan penelitian adalah (1) Mengetahui akses dan fungsi TIK bagi masyarakat pertanian, (2) Mengetahui pola penggunaan TIK untuk pertanian oleh masyarakat pertanian dan (3) Mengetahui faktor-faktor yang mempengaruhi penggunaan TIK untuk mendukung kegiatan pertanian. Metode penelitian yang digunakan adalah deskriptif analitik dengan teknik penelitian survey. Lokasi penelitian adalah kawasan pertanian komersial di Yogyakarta yang mencakup Patuk Gunungkidul, Turi Sleman, Sanden Bantul dan Panjatan Kulon Progo. Sampel dipilih dengan teknik simple random sampling. Data dikumpulkan dengan menggunakan kuesioner terstruktur, observasi dan wawancara mendalam. Analisis data dilakukan dengan menggunakan analisis statistik deskriptif dan dan regresi berganda. Hasil studi menunjukkan bahwa (1). Kepemilikan media TIK di semua lokasi kajian cukup tinggi (media konvensional dan media baru) yang mampu melayani penyediaan informasi dan hiburan, namun fungsi edukasi masih sangat terbatas, (2). Penggunaan media TIK untuk mendukung kegiatan pertanian: media konvensional (televisi radio) untuk teknis produksi, kebijakan dan pemasaran, sedangkan media baru untuk untuk informasi teknis produksi, pemasaran, kebijakan dan